Penerapan E-Parlemen di Dewan Perwakilan Rakyat Republik Indonesia - Sylvia Febrina; Lisman Manurung (Sospol : Jurnal Sosial Politik, 2022)
This study aims to explain the implementation of e-parliament through the website of Indonesia Parliament. In order to enhance the role of parliament and democratic values, modern legislatures around the world are making use of technology to bridge the enormous gap between parliamentarians and the public. Electronic parliamentary services or e-parliament are proclaimed as a concept of digital transformation and are expected to have a significant impact on three main things, namely administrative efficiency, improved access, and dissemination of information and interaction with the public. By using a mixed research method of content analysis and case studies in looking at two aspects of e-parliament which include information disclosure and participation, this study resulted in the finding that the implementation of e-parliament on the parliament's website is mostly still at the stage of providing information. Given that the parliament's website does not yet provide a simple tool for interactive communication between parliament and citizens in an effective way.